Loneliness among adult cancer survivors in the United States: prevalence and correlates - Christopher W. Wheldon; Avishek Choudhury; Bryan P. McCormick; Juan R. Albertorio-Díaz (Scientific Reports)
Abstract Loneliness is recognized as a significant public health concern, affecting quality of life and health outcomes, including cancer-related outcomes. Thus, it is essential to understand the prevalence and risk factors for loneliness in people with cancer. Through an exploratory analysis of secondary data from the Health Information National Trends Survey, we investigated the prevalence and correlates of loneliness among adult cancer survivors (N = 1,234). An estimated 35.9% of participants experienced moderate to severe loneliness. In a series of multiple logistic regression models, we identified differences in sociodemographic, cancer-related factors, non-cancer comorbidities, social isolation, social support, and social media use behaviors in the odds of reporting moderate-severe loneliness. In our fully adjusted model, years since cancer diagnosis, fair-poor overall health, moderate-high psychological distress, and having children living in the household were all positively and independently associated with moderate-severe loneliness. In this same model, being married and reporting some types of social support were negatively associated with moderate-severe loneliness. This study underscores the multifaceted nature of loneliness among cancer survivors, revealing a complex interplay of demographic, health-related, and social factors.